A framework for Exploring Iraqi tourism sites by Augmented Reality application (Eurasian Journal of Engineering and Technology, 2022)
Augmented reality is an interdisciplinary field that uses information technology and computer vision in various areas, including medicine, education, architecture, industry, tourism, etc., to enrich a real-world perspective in real-time with additional digital information. This paper aims to provide an overview of this technology, its types and tools, To promote its usage in Iraq's tourism industry. Iraq contains tourist areas, civilizations and ancient heritage places that date back thousands of years but suffer neglect due to the lack of tourism activity. This paper also presents a framework for developing a mobile augmented reality application that serves Iraqi tourism sites called IraqAR. The application works based on Markers, and it was developed by the unity game engine and Vuforia SDK. It has three key characteristics and runs on the Android platform. After the application recognizes a specific image marker or QR code, the user may explore 3D model of a sites that is related to it, listen to explanatory audio that gives a description of the chosen tourism attraction and read information about it. As a support advertising medium, the image marker or QR code printed in the form of a book. One of the applications of the Human and Computer Interaction discipline is this new method of engagement to promote tourism objects. The user will be able to learn about Iraq's tourist attractions in a new and unique way, and the site will be able to attract more motivated tourists as a consequence of this application